Fault location for distribution networks with distributed generation sources using a hybrid DE/PSO algorithm - Quan Zhou; Bolin Zheng; Caisheng Wang; Junhui Zhao; Yang Wang (Proceedings / IEEE Power Engineering Society General Meeting, 2013)
Fault location has been an important and challenging task in distribution network management. The issue has become more complicated when more distributed generation (DG) are added to distribution networks. This paper presents a fault location method by developing a new switch function to process the ON/OFF information of circuit breakers/switches for distribution networks with multiple DG sources. The proposed detection method is based on a binary hybrid algorithm of particle swarm optimization (PSO) and differential evolution (DE), which targets for solving "premature convergence" issues. It is a two-population evolution scheme with information exchange mechanism. The algorithm can adaptively accommodate the changes caused by multiple DGs. The proposed method is used to locate multiple fault sections in multi-source distribution networks. The simulation results indicate that the proposed method can identify either single or multiple faults accurately and efficiently with the tolerance capability of error messages.